A survey of bisphosphonate-related osteomyelitis/osteonecrosis of the jaws - ARIYOSHI, Yasunori; MORITA, Syosuke; FURUSAWA, Kiyofumi; IMAI, Yutaka; SHIMADA, Jun; UEYAMA, Yoshiya; SHIMAHARA, Masashi; MIZUKI, Harumi (Japanese Journal of Oral and Maxillofacial Surgery, 2007)
Bisphosphonates are used for the management of bone metastatic disease and hypercalcemia caused by malignancy, as well as the treatment of osteoporosis. Recently, a number of patients with bisphosphonate-associated osteomyelitis and osteonecrosis of the jaws have been reported in the English-language literature. This report describes patients with bisphosphonate-related osteomyelitis and osteonecrosis of the jaws in Japan. The subjects were enrolled using questionnaires sent to 239 institutions certified as training facilities by the Japanese Society of Oral and Maxillofacial Surgeons in 2006. Thirty patients (4 men and 26 women) from 18 different institutions (mean age at diagnosis, 66.9 years) were studied. As for local features, pain with or without swelling was the most common symptom and sign. The mandible was affected in 22 patients, the maxilla in 6, and both jaws in 2. Twenty patients received intravenous bisphosphonates, 8 received only oral bisphosphonates, and 1 received both types of treatment. The reasons for bisphosphonate treatment were bone metastasis from breast carcinoma (13 patients), multiple myelomas (6 patients), osteoporosis (8 patients), and hypercalcemia related to malignancy. More than 50 % of the patients underwent oral surgery including tooth extraction just before or during treatment with bisphosphonates, while 5 patients received no dental treatment. In addition to antibiotic therapy, surgery, including sequestrectomy and curettage, was performed. As for outcome, 8 of the patients were completely cured, while 17 patients remained under treatment at the time of this writing.